Research progress on dysphagia in elderly stroke patients (老年脑卒中患者吞咽功能障碍研究进展) - WANG Xuan (王轩); DENG Ying (邓颖) (Journal of International Translational Medicine Limited, 2024)
Swallowing dysfunction in elderly stroke patients is a common and significant clinical problem that has a considerable impact on their health and quality of life. Studies have indicated that impaired swallowing function in elderly stroke patients is associated with multiple factors, including the location and extent of the stroke, the degree of damage to the neural pathways, and related inflammatory responses. Interventions for swallowing dysfunction in elderly stroke patients have gradually become more diverse and individualized. This paper reviewed the studies on dysphagia in elderly stroke patients, summarized etiologic and pathophysiologic mechanisms, assessment tools, and treatment of dysphagia, and provided reference for diversifying clinical research and treatment. (吞咽功能障碍是老年脑卒中患者常见并发症, 严重影响患者预后和生活质量。老年脑卒中患者的吞咽功能受损与中风部位和范围、神经通路的受损程度以及相关的炎症反应等因素有关。随着脑卒中相关研究的深入开展, 老年脑卒中患者吞咽功能障碍的干预措施逐渐多样化和个体化。本研究主要回顾和总结老年脑卒中后吞咽功能障碍的研究进展, 包括病因和病理生理机制、评估工具以及治疗方法等方面, 以期为临床研究以及治疗的多元化提供参考。)